Effect of dietary supplementation of sodium butyrate on growth performance, survival rate and carcass composition of beluga, Huso huso - Hossein Panahi; Hossein Ouraji; Farid Firuzbakhsh; Maryam Ghiyasi (University of Guilan, 2021)
In the present study, the effects of sodium butyrate as a dietary supplement on growth performance, survival rate and carcass composition of beluga, Huso huso were evaluated. After acclimatizing to the rearing conditions feeding with the basal diet for a week, five experimental diets containing 0, 0.1, 0.2, 0.3, 0.4 and 0.5% (T0, T0.1, T0.2, T0.3, T0.4 and T0.5) sodium butyrate were examined on 360 juvenile beluga (average weight 15 ± 0.59 g) for 8 weeks. The studied fish were randomly transferred to 18 experimental 3200-L tanks and a dewatering volume of 1000 L (20 fish per tank). At the end of the trial, growth indices (final weight, weight gain, weight gain percentage, condition factor, specific growth rate, protein efficiency ratio), survival rate (%) and carcass composition were measured. The results showed that sodium butyrate supplementation influenced the growth performance, survival rate and carcass composition of the examined fish. The best growth performance and survival rate were observed in T0.3 (p<0.05). In addition, feed conversion ratio and feed efficiency in T0.3 were significantly better than the control group (p<0.05). Carcass protein of fish in T0.3 was significantly higher, while carcass fat was significantly lower than the control group (p<0.05). Overall, this study showed that 0.3% sodium butyrate supplement in the diet can enhance the growth performance, survival rate and carcass composition in juvenile beluga.